Proton Donor Acceptor Interactions of Disubstituted Thiovioluric Acids with Amines Bases - SINGH, B.R.; RANI, BABITA; SORABH SINGH, DEEP (Asian Journal of Chemistry, 2010)
The stability constants of hydrogen bonded ion pair or proton transfer complex formation of N,N'-dimethyl thiovioluric acid [DMTVA], N,N'- di-o-tolyl thiovioluric acid [DOTTVA], N,N'-di-m-tolyl thiovioluric acid [DMTTVA] and N,N'-di-p-tolyl thiovioluric acid [DPTTVA] with methyl amine, dimethyl amine, trimethyl amine, ethyl amine, diethyl amine, triethyl amine, n-butyl amine, dibutyl amine and tributyl amine have been determined spectroscopically in 95 % (v/v) ethanol. The composition of the complexes is determined in solution potentiometrically and spectrophotometrically and substantiated by the element analysis and IR spectra of the isolated complexes. The stabilities of the thiovioluric acid-amine complexes have been correlated with the base strength of amines. The correlation between the mode of enolization in the acids and the structure of the proton transfer complex is discussed. The variation in proton transfer constants of acids has been explained on the basis of the changes in the distribution of electron density in the ring.